Scale effect of storm sewage overflow structure - S. Y. Lim; K. H. M. Ali (1990)
This paper describes an investigation into the scale effect of model sizes on the particle retention efficiency of the stilling pond type storm sewage overflows. The scaling criteria for model-prototype similarity were examined. Data from previous studies on scale effect were reviewed and analysed and their shortcomings discussed. A qualitative comparison of the present model results with the prototype data obtained by Saul (1977) were presented and confirmed the findings that an increase in model size resulted in a decrease in the efficiency of a chamber